(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
During the Byzantine period, some pagan temples were converted into Christian churches; this method of reusing the temples can be found in every Christianised province, although it is not particularly widespread. It is characterized by a considerable variety both at a regional level and at the level of individual urban centres. In the Levant, the temple conversion was a quite rare phenomenon and, in the face of a great number of Roman temples and sanctuaries, only few of these have been converted into churches. However, an intensification of the conversions can be traced in the area of the Byzantine provinces of Palaestina I, Palaestina II and Arabia. This article will consider six case studies in as many urban centres from this territory, exploring common factors in order to assess the presence of shared urban patterns.